2019
DOI: 10.1007/s11920-019-1079-z
|View full text |Cite
|
Sign up to set email alerts
|

A Brief but Comprehensive Review of Research on the Alternative DSM-5 Model for Personality Disorders

Abstract: Purpose of Review Both the Alternative DSM-5 Model for Personality Disorders (AMPD) and the chapter on personality disorders (PD) in the recent version of ICD-11 embody a shift from a categorical to a dimensional paradigm for the classification of PD. We describe these new models, summarize available measures, and provide a comprehensive review of research on the AMPD. Recent Findings A total of 237 publications on severity (criterion A) and maladaptive traits (criterion B) of the AMPD indicate (a) acceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
212
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(263 citation statements)
references
References 312 publications
11
212
1
7
Order By: Relevance
“…Although there is now consistent evidence that dimensional PD classification systems are superior to categorical ones (e.g., Zimmermann et al, 2019), there is an ongoing debate about how to best conceptualize PD severity in a dimensional system (Widiger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is now consistent evidence that dimensional PD classification systems are superior to categorical ones (e.g., Zimmermann et al, 2019), there is an ongoing debate about how to best conceptualize PD severity in a dimensional system (Widiger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of the LPFS in the DSM-5 has given an impetus to research on the assessment of personality functioning ( 12 ), and it is to be expected that psychophysiological research will follow. According to the AMPD, emotional regulation, self-esteem regulation, and other self-regulatory capacities are closely related to interpersonal functioning, like the capacity to understand others' intentions and emotions, and the capacity to engage in close relationships.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Anxiousness; (c) Separation insecurity; (d) Depressivity; (e) Impulsivity; (f) Risk taking; and (g) Hostility. Research on the AMPD BPD diagnosis has shown adequate continuity with Section II BPD diagnosis (see [24] for a summary).…”
Section: Introductionmentioning
confidence: 99%